The ambivalent relation between state and illegal actors: piracy retail in Mexico A relação ambígua entre o Estado e os atores ilegais: o mercado da pirataria no México - José Carlos G. Aguiar (Etnográfica: Revista do Centro em Rede de Investigação em Antropologia, 2011)
In the rise of democratic governments across Latin America, the neoliberal law-and-order perspective has been the most influential model of security in the region. This approach is based on the opposition between state and illegal agents, as if they were two different sets of actors. Influenced by this model, Mexican president Vicente Fox launched an extensive anti-piracy programme to eradicate retail of counterfeit. Based on ethnographic material gathered in the San Juan de Dios market in Guadalajara, I discuss on the exchanges between piracy sellers and police officers. My argument is that law enforcement programmes have not affected the political economy of corruption, they overlook the net of ambiguous loyalties where state and illegal actors are entrenched. The anthropology of the state provides the rationale for a critique on neoliberal security policies. Quando surgiram os governos democráticos na América Latina, a perspetiva neoliberal da lei e da ordem constituiu-se como o modelo de segurança dominante na região. Esta abordagem baseia-se na oposição entre o Estado e os agentes da ilegalidade, como se fossem dois conjuntos de atores distintos. Influenciado por este modelo, o presidente mexicano Vicente Fox lançou um programa alargado contra a pirataria, pretendendo erradicar a venda da contrafação. A partir de material etnográfico recolhido no mercado de San Juan de Dios, em Guadalajara, examino as interações entre vendedores de mercadoria pirata e agentes da polícia. Argumento que os programas para a aplicação da lei não afetaram a economia política da corrupção e que ignoram a rede de lealdades ambíguas que envolvem o Estado e os atores ilegais. A antropologia do Estado oferece os princípios para uma crítica sobre as políticas de segurança neoliberais.